Application Of The Discussion Method To Improve The Learning Outcomes Of Indonesian Class V Elementary School Students - Widyawati, Gati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The application of the discussion method to improve the results of learning Indonesian for fifth grade elementary school students regarding key word material in print media advertisements is still lacking, namely out of 27 students only 13 students achieve the minimum completeness criteria (KKM) 67. Based on these conditions the teacher makes efforts so that student learning outcomes can be increased, namely by taking action in the form of using the discussion method in learning activities. The purpose of this study was to improve student learning outcomes in the Indonesian language lesson content on Keywords in Print Media Advertising which was carried out using the Classroom Action Research method. Data collection techniques were carried out using tests and non-tests, with data collection tools in the form of assignment sheets, post-test sheets, and observation sheets both by the teacher towards students and teachers by collaborators. The results showed that there was a significant increase in the learning outcomes of fifth grade students after the action was held, when compared to their learning outcomes before the action was held. The use of the discussion method in learning can improve the learning outcomes of the Indonesian language lesson content Key Words in Print Media Advertisements for fifth grade elementary school students.